2006
DOI: 10.1016/j.febslet.2006.06.043
|View full text |Cite
|
Sign up to set email alerts
|

Disturbance of cerebellar synaptic maturation in mutant mice lacking BSRPs, a novel brain‐specific receptor‐like protein family

Abstract: By DNA cloning, we have identified the BSRP (brainspecific receptor-like proteins) family of three members in mammalian genomes. BSRPs were predominantly expressed in the soma and dendrites of neurons and localized in the endoplasmic reticulum (ER). Expression levels of BSRPs seemed to fluctuate greatly during postnatal cerebellar maturation. Triple-knockout mice lacking BSRP members exhibited motor discoordination, and Purkinje cells (PCs) were often innervated by multiple climbing fibers with different neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(92 citation statements)
references
References 30 publications
3
88
0
Order By: Relevance
“…S1D). Finally, in accordance with the published report of a predominant neuronal expression of SEZ6L2 (Miyazaki et al, 2006), we mainly detected SEZ6L2 in the mouse brain, and found that it was expressed endogenously in a mouse neuroblastoma cell line (N1E-115) (Fig. 1B).…”
Section: Identification Of Sez6l2 As a New Cathepsin-d-binding Partnersupporting
confidence: 77%
See 3 more Smart Citations
“…S1D). Finally, in accordance with the published report of a predominant neuronal expression of SEZ6L2 (Miyazaki et al, 2006), we mainly detected SEZ6L2 in the mouse brain, and found that it was expressed endogenously in a mouse neuroblastoma cell line (N1E-115) (Fig. 1B).…”
Section: Identification Of Sez6l2 As a New Cathepsin-d-binding Partnersupporting
confidence: 77%
“…This finding, coupled with neuron-specific expression of SEZ6L2 (Miyazaki et al, 2006), and with the reported observation that cathepsin D binding to LRP1 in fibroblasts promotes their outgrowth (Beaujouin et al, 2010), suggest a cell type specificity of some alternatives to the Man-6-P transport pathways and linkage of these pathways to specific cellular processes.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Proteins of the Seizure protein 6 (Sez6) family are abundant in neurons and are localized to the somatodendritic compartment of these highly polarised cells (Gunnersen et al, 2007;Miyazaki et al, 2006). Two recent studies (Kuhn et al, 2012;Pigoni et al, 2016) highlight the important role of the Alzheimer's disease (AD)-linked aspartyl-protease β-site amyloid precursor protein (APP) cleaving enzyme 1 (BACE1) in the regulation of Sez6 and Sez6-like (Sez6L), influencing their sub-cellular distribution and, presumably, their function.…”
Section: Seizure-6 Proteins Highlight Bace1 Functions In Neurobiologymentioning
confidence: 99%